2005
DOI: 10.1007/s00425-005-1498-4
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence of black cottonwood (Populus trichocarpa) reveals 18 conserved cellulose synthase (CesA) genes

Abstract: The genome sequence of Populus trichocarpa was screened for genes encoding cellulose synthases by using full-length cDNA sequences and ESTs previously identified in the tissue specific cDNA libraries of other poplars. The data obtained revealed 18 distinct CesA gene sequences in P. trichocarpa. The identified genes were grouped in seven gene pairs, one group of three sequences and one single gene. Evidence from gene expression studies of hybrid aspen suggests that both copies of at least one pair, CesA3-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 36 publications
4
91
0
1
Order By: Relevance
“…Phylogenetic analysis reveals that these unique components, in the primary and secondary cell walls, represent distinct gene families that diverged early in the evolution of land plants (Holland et al, 2000;Samuga and Joshi, 2002;Tanaka et al, 2003;Burton et al, 2004;Djerbi et al, 2005;Nairn and Haselkorn, 2005;Ranik and Myburg, 2006;Suzuki et al, 2006;Kumar et al, 2009;Carroll and Specht, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis reveals that these unique components, in the primary and secondary cell walls, represent distinct gene families that diverged early in the evolution of land plants (Holland et al, 2000;Samuga and Joshi, 2002;Tanaka et al, 2003;Burton et al, 2004;Djerbi et al, 2005;Nairn and Haselkorn, 2005;Ranik and Myburg, 2006;Suzuki et al, 2006;Kumar et al, 2009;Carroll and Specht, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis revealed six distinct CESA clades found in seed plants, each corresponding to one of the six required components of the primary and secondary cellulose synthase complexes in Arabidopsis (Holland et al, 2000;Samuga and Joshi, 2002;Tanaka et al, 2003;Burton et al, 2004;Djerbi et al, 2005;Nairn and Haselkorn, 2005;Ranik and Myburg, 2006;Suzuki et al, 2006;Kumar et al, 2009;Carroll and Specht, 2011). The interaction between the different CESA proteins in the primary and secondary rosettes has been characterized previously by coimmunoprecipitation and yeast two-hybrid methods, showing interaction patterns with similarities between primary and secondary CESAs (Taylor et al, 2000;Desprez et al, 2007;Wang et al, 2008;Atanassov et al, 2009;Timmers et al, 2009).…”
mentioning
confidence: 83%
“…We used sequences encoded by the identified CesA or Csl genes in Arabidopsis 25 , poplar 44,45 , rice 46 , maize 26 and sorghum 24 for alignment to those encoded by the gene models of Brachypodium and bamboo by BLASTP with E values under 1 × 10 -10 . Aligned hits with at least 200 amino acids of matched length and over 50% protein sequence identity were considered to be homologs of the CesA or Csl genes.…”
Section: Competing Financial Interestsmentioning
confidence: 99%
“…The CesA gene family has ten members in Arabidopsis (Richmond and Somerville 2000), while Populus has 18 expressed CesA genes (Djerbi et al 2005;Suzuki et al 2006;Kumar et al 2009). A phylogenetic analysis of the Populus CesA gene family revealed that the 18 CesA genes grouped with the ten Arabidopsis orthologs in all of the primary and secondary cell wall related clades and that Populus has two or more paralogs of some Arabidopsis genes (Kumar et al 2009).…”
Section: Introductionmentioning
confidence: 99%